Tests and efficiency of A.T.B.G.E alternator - Nash, Albert Marvin; Morlan, Samuel Erwin (My University, 1904)
Introduction: In the fall of 1831, Michael Faraday discovered the “electro-magnetic induction of currents.” His discovery was communicated to the Royal Society November 24th of the same year. A discussion of these experiments appears in the first volume of Faraday’s Experimental Researches in Electricity. He first induced currents in a coil, by starting and stopping a current in a near by coil, next he induced a current in a coil, by moving it rapidly past the ends of a powerful horse-shoe magnet, the direction of flow of the current depending on the direction of motion and finally he constructed the first known dynamo. The following figure illustrates his electrical machine. Fig. 1. This machine was made by mounting a copper disc twelve inches in diameter and one fifth of an inch thick, on a brass axle. The disc was placed so as to be revolved between the poles of a horse-shoe magnet. The current…
Test and efficiency of polyphase alternator
Citation: Nash, Albert Marvin and Morlan, Samuel Erwin. Tests and efficiency of A.T.B.G.E alternator. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Alternators; Currents; Induction; Electrical Engineering; Theses